2011
DOI: 10.1007/s10750-011-0738-9
|View full text |Cite
|
Sign up to set email alerts
|

Plants used in constructed wetlands with horizontal subsurface flow: a review

Abstract: The presence of macrophytes is one of the most conspicuous features of wetlands and their presence distinguishes constructed wetlands from unplanted soil filters or lagoons. The macrophytes growing in constructed wetlands have several properties in relation to the treatment process that make them an essential component of the design. However, only several roles of macrophytes apply to constructed wetlands with horizontal subsurface flow (HF CWs). The plants used in HF CWs designed for wastewater treatment shou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
244
1
24

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 550 publications
(300 citation statements)
references
References 146 publications
(110 reference statements)
10
244
1
24
Order By: Relevance
“…With regard to COD, TN and TOC, it was found that the CW1 (SF-CW) and CW6 (HSSF-CW without plants) performed worse than the other four CWs including two HSSF-CWs and two VSSF-CWs. Subsurface flow and planting were beneficial to the removal of nutrients, which is consistent to some previous studies (Brix, 1994;Lin et al, 2002b;Wen et al, 2010;Vymazal, 2011;Carvalho et al, 2014). For 8 detected antibiotics, CW4 and CW5 (HSSF-CWs with different plants) performed better than the other four CWs, with CW1 being the worst (Fig.…”
Section: Performance Comparison Among the Mesocosm-scale Cwssupporting
confidence: 91%
“…With regard to COD, TN and TOC, it was found that the CW1 (SF-CW) and CW6 (HSSF-CW without plants) performed worse than the other four CWs including two HSSF-CWs and two VSSF-CWs. Subsurface flow and planting were beneficial to the removal of nutrients, which is consistent to some previous studies (Brix, 1994;Lin et al, 2002b;Wen et al, 2010;Vymazal, 2011;Carvalho et al, 2014). For 8 detected antibiotics, CW4 and CW5 (HSSF-CWs with different plants) performed better than the other four CWs, with CW1 being the worst (Fig.…”
Section: Performance Comparison Among the Mesocosm-scale Cwssupporting
confidence: 91%
“…This contribution of plants is consistent with the effects on removal of other xenobiotics by other species in LECA beds (Dordio et al, 2009b(Dordio et al, , 2010. In addition to other more basic roles of plants in CW operation (Brix, 1997;Vymazal, 2011), these results demonstrate the potential for an equally important and active role played by the vegetation in the removal of specific organic pollutants such as MCPA, which enables the performance of planted systems to surpass that of a simpler LECA filter setup. Due to the moderate lipophilicity of MCPA, as expressed by its octanol-water partition coefficient (log K ow = 1.37-1.43 (Montgomery, 1993)), it is likely that plants have an active role in the removal of this compound through direct uptake.…”
Section: Mcpa Removal Efficiencysupporting
confidence: 77%
“…In CWs designed to treat eutrophic water, the main goal of vegetation is to reduce solar radiation, thus limiting phytoplankton growth and promoting its decomposition and sedimentation. Other important functions of vegetation in CWs are as follows: reduction of water current, mitigation of wind velocity, induction of sedimentation and prevention of sediment resuspension, active nutrient uptake and retention within the biomass, provision of surface for periphyton growth, and oxygen transport to sediment both during the active growth phase and through the death culms (Vymazal, 2011 ). The vegetation cover can also add aesthetic values contributing to the landscaper quality.…”
Section: Aq2mentioning
confidence: 99%